ChemInform Abstract: Palladium‐Catalyzed Regioselective C—H Acetoxylation of 2‐Aryloxypyridines with 2‐Pyridyloxy as a Removable Directing Group. Issue 46 (27th October 2016) - Wang, Liang; Pan, Liang; Huang, Yibo; Chen, Qun; He, Mingyang
Abstract: Yields of mono‐ as well as bis‐acetoxylated arenes depend significantly on the electronic nature of aryl substituents.